Espacialização das estimativas de contaminação de águas subterrâneas por Tebuthiuron - Moraes, Diego Augusto de Campos [UNESP]; Zimback, Célia Regina Lopes [UNESP]; Spadotto, Claudio Aparecido [UNESP] (My University, 2012)
Improper use of pesticides can lead to significant environmental impacts such as, contamination of environmental compartments, being the aquatic compartments the most vulnerable. In this context, the spatialization of pesticides concentrations estimative in groundwater provides important insights for decision making in managing and monitoring pesticides use. This study aimed to spatialize estimatives of groundwater contamination by Tebuthiuron, from different irrigation depths in the Rio Pardo basin, Pardinho-SP, Brazil. The simulations were performed using the ARAquá computer system, considering 0mm, 200 mm and 400 mm annual irrigation depths. Geostatistical techniques were used to obtain the spatial distribution of the simulated estimative. Tebuthiuron maps estimating concentration in groundwater were obtained by Kriging interpolation method, and indicated the areas with high potential for groundwater contamination. Considering all the simulations, it was concluded that there was no risk of groundwater contamination by Tebuthiuron in the study area.

O uso inadequado de defensivos agrícolas pode levar a impactos ambientais relevantes, como a contaminação de diversos compartimentos ambientais, sendo os mais vulneráveis, os compartimentos aquáticos. Nesse contexto, a espacialização das estimativas de concentração de defensivos agrícolas na água subterrânea fornece importantes subsídios para a tomada de decisão no gerenciamento e monitoramento do uso de defensivos agrícolas. Assim, este trabalho teve por objetivo espacializar as estimativas de contaminação de águas subterrâneas por Tebuthiuron, considerando diferentes lâminas de irrigação na Bacia do Rio Pardo, Pardinho-SP. As simulações realizadas com o sistema computacional ARAquá considerando as lâminas de irrigação anuais de 0 mm, 200 mm e 400 mm. Técnicas geoestatísticas foram utilizadas em conjunto com as simulações para obter a espacialização dessas estimativas. Foram obtidos os mapas das estimativas de concentração de defensivos agrícolas na água subterrânea pelo método de interpolação por krigagem, sendo que estes indicaram as áreas com maior potencial de contaminação da água subterrânea. Considerando todas as simulações pode-se concluir que não houve risco de contaminação da água subterrânea por Tebuthiuron. As técnicas de geoestatística contribuíram fortemente para a espacialização das estimativas de concentração de defensivos agrícolas na água subterrânea.
Estimatives of groundwater contamination spatialization by Tebuthiuron
Keywords: Geoestatistical; Maps; Simulations; computer simulation; concentration (composition); decision making; environmental impact; environmental risk; geostatistics; groundwater pollution; irrigation; kriging; mapping method; pesticide; pollution monitoring; spatial distribution; Brazil; Pardo Basin; Sao Paulo [Brazil]